CDK4/6 Inhibition – Therapy Sequences and the Quest to Find the Best Biomarkers – an Overview of Current Programs - Schneeweiss, Andreas; Brucker, Sara Y.; Huebner, Hanna; Volmer, Lea L.; Hack, Carolin C.; Seitz, Katharina; Ruebner, Matthias; Heublein, Sabine; Thewes, Verena; Lüftner, Diana; Lux, Michael P.; Jurhasz-Böss, Ingolf; Taran, Florin-Andrei; Wimberger, Pauline; Anetsberger, Daniel; Beierlein, Milena; Schmidt, Marcus; Radosa, Julia; Müller, Volkmar; Janni, Wolfgang; Rack, Brigitte; Belleville, Erik; Untch, Michael; Thill, Marc; Ditsch, Nina; Aktas, Bahriye; Nel, Ivonne; Kolberg, Hans-Christian; Engerle, Tobias; Tesch, Hans; Roos, Christian; Budden, Christina; Neubauer, Hans; Hartkopf, Andreas D.; Fehm, Tanja N.; Fasching, Peter A. (Geburtshilfe und Frauenheilkunde, 2024)
In recent years, new targeted therapies have been developed to treat patients with hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2−) breast cancer. Some of these therapies have not just become the new therapy standard but also led to significantly longer overall survival rates. The cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6i) have become the therapeutic standard for first-line therapy. Around 70 – 80% of patients are treated with a CDK4/6i. In recent years, a number of biomarkers associated with progression, clonal selection or evolution have been reported for CDK4/6i and their endocrine combination partners. Understanding the mechanisms behind treatment efficacy and resistance is important. A better understanding could contribute to planning the most effective therapeutic sequences and utilizing basic molecular information to overcome endocrine resistance. One study with large numbers of patients which aims to elucidate these mechanisms is the Comprehensive Analysis of sPatial, TempORal and molecular patterns of ribociclib efficacy and resistance in advanced Breast Cancer patients (CAPTOR BC) trial. This overview summarizes the latest clinical research on resistance to endocrine therapies, focusing on CDK4/6 inhibitors and discussing current study concepts.Für Patientinnen wie auch Patienten mit hormonrezeptorpositivem (HRpos)/Human epidermal growth factor receptor 2-negativem (HER2neg) Mammakarzinom wurden in den letzten Jahren einige neue, zielgerichtete Therapien eingeführt. Einige dieser Behandlungen konnten sich nicht nur als neuer Therapiestandard etablieren, sondern führten auch zu einem signifikant verlängerten Gesamtüberleben. Insbesondere die Cyclin-dependent Kinase 4 and 6 Inhibitors (CDK4/6i) haben sich als Therapiestandard in der ersten Therapielinie etabliert. Insgesamt 70 – 80% der Patientinnen werden mit einem CDK4/6i behandelt. Sowohl für die CDK4/6i als auch für die endokrinen Kombinationspartner wurden in den letzten Jahren zunehmend Biomarker beschrieben, die mit einem Progress oder einer klonalen Selektion oder Evolution assoziiert sind. Vor diesem Hintergrund ist die Kenntnis um Effektivitäts- und Resistenzmechanismen von besonderer Bedeutung. Dieses Wissen könnte wegweisend sein, um die effektivsten Sequenzen zu planen und molekulare Grundlagen für das Überwinden der endokrinen Resistenz zu nutzen. Eine der Studien, die mit einer großen Fallzahl dazu beitragen soll, diese Mechanismen zu erforschen, ist die Comprehensive Analysis of sPatial, TempORal and molecular patterns of ribociclib efficacy and resistance in advanced Breast Cancer patients (CAPTOR BC)-Studie. Diese Übersichtsarbeit fasst den aktuellen Stand der klinischen Forschung zur Resistenz gegen endokrine Therapien mit Fokus auf CDK4/6-Inhibitoren zusammen und erörtert aktuelle Studienkonzepte.
Keywords: breast cancer; therapy; CDK4/6